User Attitude Towards the Library Resources and Services in the Nursing Colleges of Karaikal Region - Preethi, M.; Vijayakumar, Dr. K. (South Eastern European Journal of Public Health, 2025)
The study examines the attitudes of nursing students and faculty members toward library resources and services in nursing colleges located in the Karaikal region. Libraries play a critical role in nursing education, providing essential resources for research, clinical practice, and academic advancement. Understanding user attitudes helps in enhancing library services to meet user needs more effectively. This research employs quantitative methodology to analyse the satisfaction level and usage patterns of library resources. The study reveals that while users generally appreciate the availability of resources, there are significant gaps in digital access, specialized nursing collections, and user-centred services.